Undergraduate medical students’ readiness for online learning at a South African university: Implications for decentralised training - A M Ingratta; S E Mabizela; A Z George; L Green-Thompson (African Journal of Health Professions Education, 2022)
Background. Decentralised teaching has the potential to transform medical education but requires greater use of online learning to address some of the challenges of decentralised teaching in low- and middle-income countries. Given the digital divide that exists in South Africa (SA), it is necessary to establish the extent of student readiness for the broader implementation of online learning.